Infigratinib in children with achondroplasia: the PROPEL and PROPEL 2 studies. (March 2022) - Savarirayan, Ravi; De Bergua, Josep Maria; Arundel, Paul; McDevitt, Helen; Cormier-Daire, Valerie; Saraff, Vrinda; Skae, Mars; Delgado, Borja; Leiva-Gea, Antonio; Santos-Simarro, Fernando; Salles, Jean Pierre; Nicolino, Marc; et al.
Background: Achondroplasia is the most common short-limbed skeletal dysplasia resulting from gain-of-function pathogenic variants in fibroblast growth factor receptor 3 ( FGFR3 ) gene, a negative regulator of endochondral bone formation. Most treatment options are symptomatic, targeting medical complications. Infigratinib is an orally bioavailable, FGFR1–3 selective tyrosine kinase inhibitor being investigated as a direct therapeutic strategy to counteract FGFR3 overactivity in achondroplasia. Objectives: The main objective of PROPEL is to collect baseline data of children with achondroplasia being considered for future enrollment in interventional studies sponsored by QED Therapeutics. The objectives of PROPEL 2 are to obtain preliminary evidence of safety and efficacy of oral infigratinib in children with achondroplasia, to identify the infigratinib dose to be explored in future studies, and to characterize the pharmacokinetic (PK) profile of infigratinib and major metabolites. Design: PROPEL (NCT04035811) is a prospective, noninterventional clinical study designed to characterize the natural history and collect baseline data of children with achondroplasia over 6−24 months. PROPEL 2 (NCT04265651), a prospective, phase II, open-label study of infigratinib in children with achondroplasia, consists of a dose-escalation, dose-finding, and dose-expansion phase to confirm the selected dose, and a PK substudy. Methods and analysis: Children aged 3−11 years with achondroplasia who completed ⩾6 months in PROPEL are eligible for PROPEL 2. Primary endpoints include treatment-emergent adverse events and change from baseline in annualized height velocity. Four cohorts at ascending dose levels are planned for dose escalation. The selected dose will be confirmed in the dose-expansion phase. Ethics: PROPEL and PROPEL 2 are being conducted in accordance with the International Conference on Harmonization Good Clinical Practice guidelines, principles of the Declaration of Helsinki, and relevant human clinical research and data privacy regulations. Protocols have been approved by local health authorities, ethics committees, and institutions as applicable. Parents/legally authorized representatives are required to provide signed informed consent; signed informed assent by the child is also required, where applicable. Discussion: PROPEL and PROPEL 2 will provide preliminary evidence of the safety and efficacy of infigratinib as precision treatment of children with achondroplasia and will inform the design of future studies of FGFR-targeted agents in achondroplasia. Registration: ClinicalTrials.gov: NCT04035811; NCT04265651.